Firm Productivity in Bangladesh Manufacturing Industries - Fernandes, Ana Margarida (World Bank, Washington, DC, 2012)
The author studies the determinants of total factor productivity (TFP) for manufacturing firms in Bangladesh using data from a recent survey. She obtains TFP measures by making use of firm-specific deflators for output and inputs. Controlling for industry, location, and year fixed effects, she finds that: (1) firm size and TFP are negatively correlated; (2) firm age and TFP exhibit an inverse-U shaped relationship; (3) TFP improves with the quality of the firm's human capital; (4) global integration improves TFP; (5) firms with research and development activities and quality certifications have higher TFP, while more advanced technologies improve TFP only in the presence of significant absorptive capacity; (6) power supply problems cost firms heavily in terms of TFP losses; and (7) the presence of crime dampens TFP.